Improving Spectrum Efficicency of 5G Network - Otunniyi, Temidayo Oluwafunke; Ovono, Bertille Auyane Ngouessy Ep (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
High peak-to-average power ratio (PAPR) is a major limitation of orthogonal frequency division multiplexing (OFDM), making it less suitable for achieving high spectrum efficiency in 5G networks. The impact of PAPR on spectrum efficiency and bit error rate (BER) is particularly critical. To address this challenge and enhance 5G performance, a spectrum-efficient cosine-modulated filter bank with tone companding method (CM-FBMC TCM) was developed and evaluated. Simulations were carried out in the MATLAB 2021 environment, with the CM-FBMC TCM model tested across three iterations. The baseline CM-FBMC exhibited a PAPR value of 16.9 dB, while the proposed CM-FBMC TCM achieved significant reductions: 7.3 dB in iteration 1, 3.8 dB in iteration 2, and 2.9 dB in iteration 3. In terms of error performance, CM-FBMC TCM reduced BER by approximately 50% compared to the conventional CM-FBMC. However, BER performance in iteration 3 deteriorated relative to iterations 1 and 2. Overall, the results indicate that CM-FBMC TCM IT3 achieved the lowest PAPR, approaching the ideal 3 dB range for multi-carrier signals in 5G systems. Nonetheless, this improvement in PAPR came at the cost of increased BER compared with earlier iterations, highlighting a trade-off between PAPR reduction and BER performance.